2012
DOI: 10.1089/vbz.2011.0613
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salmonella Movement Through the Gut of the Lesser Mealworm, Alphitobius diaperinus (Coleoptera: Tenebrionidae)

Abstract: Understanding the sources and contribution of reservoir populations of pathogens in poultry production operations is important for development of biosecurity measures to mitigate their transfer. A. diaperinus are prevalent in production operations and difficult to suppress. Management standards accept the reutilization of litter in which insects survive between flock rotations. Removing litter and spreading it onto nearby fields results in the inadvertent dispersal of beetles. Few studies demonstrating the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…; Zheng et al . ). Recently, the use of GFP‐tagged marker bacteria has elucidated the mechanisms involved in the vectoring and transmission of Salmonella and subsequently the infection of poultry flocks within poultry production facilities (Crippen et al .…”
Section: Public Health Concerns – Safety Issuesmentioning
confidence: 97%
“…; Zheng et al . ). Recently, the use of GFP‐tagged marker bacteria has elucidated the mechanisms involved in the vectoring and transmission of Salmonella and subsequently the infection of poultry flocks within poultry production facilities (Crippen et al .…”
Section: Public Health Concerns – Safety Issuesmentioning
confidence: 97%
“…Although unintentional, the dissemination of pathogens may be facilitated by these practices, as well as the retention of pathogens between flock rotations, because of the pervasive presence of this arthropod. The spatial and temporal dispersal of Salmonella at these facilities has been established primarily in laboratory studies or by indirect field observations (Crippen et al., , ; Davies & Wray, ; Harein, de las Casas, Pomeroy, & York, ; McAllister, Steelman, & Skeeles, ; Roche et al., ; Zheng et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of Salmonella remaining in and on the LMB after shedding did not significantly change over 24 hr indicating maintenance of the Salmonella load. As we know that the mean gut transit time of Salmonella in the LMB is 3–5 hr, it indicates the likelihood of recontamination of the LMB, as well as possibly transient colonization within the LMB and the possible perpetuation of Salmonella infection within the facilities (Crippen et al., ; Zheng et al., ). The LMB readily acquired Salmonella from the contaminated manure, and the transfer from manure to LMB was significant at a lower bacterial load (10 5 cfu/ml) than the transfer from LMB to manure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the harsh conditions encountered in the insect midgut (such as extreme pH, presence of digestive enzymes, redox potential, and ionic strength) and the activation of defense mechanisms in response to foreign organisms normally inhibit the establishment and survival of ingested microorganisms (25,26). Previous studies have shown successful gut migration of S. enterica in synanthropic and coprophagic insects (27)(28)(29). However, the fates of ingested bacteria varied significantly among species of insects, indicating that only certain species offer favorable conditions that allow movement and retention of S. enterica in the alimentary canal.…”
Section: Discussionmentioning
confidence: 99%